Dietary calcium, phosphorus, and potassium intake associated with erectile dysfunction in the National Health and Nutrition Examination Survey (NHANES) 2001 to 2004 - Deng, Chen-Yuan; Ke, Xin-Peng; Guo, Xu-Guang (PloS one, 2024)
Erectile dysfunction is now a common disorder of sexual function, and its relationship to dietary calcium, phosphorus, and potassium has not been well studied. We set out to determine if dietary intakes of calcium, phosphorus, and potassium are related to erectile dysfunction in U.S. men. For this cross-sectional investigation, we used data from NHANES 2001-2004. To investigate the connection of dietary calcium, phosphorus, and potassium intake with erectile dysfunction, we employed multivariate logistic regression, smoothed curve fitting, and subgroup analysis. This cross-sectional study comprised 3,556 eligible male subjects in total, with a weighted mean age of 49.93±18.13 years. After controlling for race and age, the greatest tertile of calcium consumption was found to have a 34% lower risk of erectile dysfunction than the lowest tertile (OR = 0.66; 95% CI = 0.52-0.84; p = 0.0006). The risk of erectile dysfunction was found to be reduced by 33% (OR = 0.67; 95% CI = 0.52-0.87; p = 0.0024) for the highest tertile of phosphorus intake compared to the lowest tertile of phosphorus intake and by 35% (OR = 0.65; 95% CI = 0.50-0.83; p = 0.0006) for the highest tertile of potassium intake compared to the lowest tertile of potassium intake in the fully adjusted model. Erectile dysfunction and dietary consumption of calcium, phosphorus, and potassium are inversely associated with the U.S. population. To confirm the accuracy of our findings, additional prospective studies are necessary. Furthermore, it is imperative to do further fundamental research at the molecular level to gain a deeper understanding of the underlying mechanisms.